Sustainable production lot sizing problem: A sensitivity analysis on controlling carbon emissions through green investment. (July 2022) - Hashan Md Mashud, Abu; Roy, Dipa; Daryanto, Yosef; Mishra, Umakanta; Tseng, Ming-Lang
Graphical abstract: Highlights: This study contributes to the production system through balanced transportation. A complete view of carbon reduction is provided by linking the production system. Proper management of waste and the deterioration of products has been studied. Simultaneous investment in preservation, green technology, and setup cost explored. Abstract: Improving inventory decisions and developing better approaches to invest green technology have been the prime contributions in the existing relevant literature. Besides proposing better inventory decisions and investing on green technologies, the financial performance of a business have also been considered as a focal point. However, none of the existing works on sustainable lot-sizing has considered a simultaneous reduction of carbon emission, product deterioration rate and set-up costs to maximize total profit. Thence, a sustainable lot-sizing model is proposed in this work by incorporating strategies to reduce the setup cost, to optimize the inventory of a greenhouse farm and simultaneous investments in green and preservation technologies to deal with the carbon emission and waste. This study shows the variation of total profit due to changes in investment level and production cycle length. The numerical examples demonstrates the threshold for green technology investment. The study also proves the vital role of preservation technology in deteriorating product inventory, as it gives a higher impact than the other investments.